ASSESSMENT OF UNDERGRADUATE STUDENTS’ METACOGNITIVE SKILLS FOR E-LEARNING IN NIGER STATE, NIGERIA - Umaru, Yunusa; Abdulwahid, Umma (Sokoto Educational Review, 2015)
This study was designed to assess undergraduate students’ metacognitive skill for e-Learning. It adopted a descriptive survey approach to determine the extent that undergraduate students in Nigeria deploy metacognitive skills for e-learning. Two research questions and two null hypotheses were stated to guide the study. Three institutions in Niger state were purposively selected and a total of 287 students were used for the study. The Metacognitive Skill f o r E-learning Questionnaire (MSELQ) was used for data collection. The instrument wav validated and the reliability tested. Data an analysis was conducted using the mean and standard deviations and t-test statistic. The findings of the study revealed that most of the students use the metacognitive skills. However, the extent of use of skill was low. Gender has no significant influence on problem and uses of metacognitive skills on e-leaning. It was recommended that for effective e-learning, students need appropriate instructions in the utilization of metacognitive skills for effective e- learning through internet.